Late gestation immune activation increases IBA1-positive immunoreactivity levels in the corpus callosum of adult rat offspring. (August 2018) - Duchatel, Ryan J.; Meehan, Crystal L.; Harms, Lauren R.; Michie, Patricia T.; Bigland, Mark J.; Smith, Doug W.; Walker, Frederick R.; Jobling, Phillip; Hodgson, Deborah M.; Tooney, Paul A.
Highlights: Maternal immune activation did not affect cortical Iba1, Gfap, IL1-β and TNF-α mRNA levels in the offspring. Maternal immune activation during late gestation increased IBA1, but not GFAP immunoreactive material in the corpus callosum of the offspring. Maternal immune activation did not alter cortical IBA1 or GFAP immunoreactive material in the offspring. Abstract: Animal models of maternal immune activation study the effects of infection, an environmental risk factor for schizophrenia, on brain development. Microglia activation and cytokine upregulation may have key roles in schizophrenia neuropathology. We hypothesised that maternal immune activation induces changes in microglia and cytokines in the brains of the adult offspring. Maternal immune activation was induced by injecting polyriboinosinic:polyribocytidylic acid into pregnant rats on gestational day (GD) 10 or GD19, with brain tissue collected from the offspring at adulthood. We observed no change in Iba1, Gfap, IL1-β and TNF-α mRNA levels in the cingulate cortex (CC) in adult offspring exposed to maternal immune activation. Prenatal exposure to immune activation had a significant main effect on microglial IBA1-positive immunoreactive material (IBA1+IRM) in the corpus callosum; post-hoc analyses identified a significant increase in GD19 offspring, but not GD10. No change in was observed in the CC. In contrast, maternal immune activation had a significant main effect on GFAP+IRM in the CC at GD19 (not GD10); post-hoc analyses only identified a strong trend towards increased GFAP+IRM in the GD19 offspring, with no white matter changes. This suggests late gestation maternal immune activation causes subtle alterations to microglia and astrocytes in the adult offspring.